2011
DOI: 10.1590/s0073-47212011000200008
|View full text |Cite
|
Sign up to set email alerts
|

Descripción del postcráneo de Rhipidomys austrinus y Graomys griseoflavus (Rodentia, Cricetidae, Sigmodontinae)

Abstract: ABSTRACT. Postcranial description of Rhipidomys austrinus and Graomys griseoflavus (Rodentia, Cricetidae, Sigmodontinae). We described the postcranial skeleton of two species of sigmodontine rodents, Rhipidomys austrinus Thomas, 1921 and Graomys griseoflavus (Waterhouse, 1837). Each structure of the postcranial skeleton is here described in details of shape, size, surface, and orientation. The skeletal anatomy of these two species shows morphological characters associated with different patterns related to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…On the other hand, the postcranial elements of the forelimbs and hind limbs of the four species of the genus show an anatomical plan related to the mode of terrestrial life, consistent with what was observed in other rodents and marsupials, for example the posterior extension of the humeral head forming a “peak”, the tubercles not surpassing the head, the separation between the trochlea and the capitulum, the flat or just concave articular surface of the radial notch in the ulna, the diaphysis of the radio curved, the extension of the greater trochanter above the femoral head, the posterior or posteromedial position of the third trochanter, and the asymmetry between the lateral and medial condyles, with the lateral wider (Hatt 1932; Sargis 2002a, b; Argot 2003; Candela and Picasso 2008; Flores and Diaz 2009; Olivares 2009; Carrizo and Diaz 2011). However, because the genus Tympanoctomys is semi-fossorial and scratch digging, characteristics in their long bones were expected which reflected their digging habit (Elissamburu and Vizcaino 2004; Morgan and Verzi 2006; Samuels and Van Valkenburgh 2008, 2009; Salton and Sargis 2008; Hopkins and Davis 2009).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the postcranial elements of the forelimbs and hind limbs of the four species of the genus show an anatomical plan related to the mode of terrestrial life, consistent with what was observed in other rodents and marsupials, for example the posterior extension of the humeral head forming a “peak”, the tubercles not surpassing the head, the separation between the trochlea and the capitulum, the flat or just concave articular surface of the radial notch in the ulna, the diaphysis of the radio curved, the extension of the greater trochanter above the femoral head, the posterior or posteromedial position of the third trochanter, and the asymmetry between the lateral and medial condyles, with the lateral wider (Hatt 1932; Sargis 2002a, b; Argot 2003; Candela and Picasso 2008; Flores and Diaz 2009; Olivares 2009; Carrizo and Diaz 2011). However, because the genus Tympanoctomys is semi-fossorial and scratch digging, characteristics in their long bones were expected which reflected their digging habit (Elissamburu and Vizcaino 2004; Morgan and Verzi 2006; Samuels and Van Valkenburgh 2008, 2009; Salton and Sargis 2008; Hopkins and Davis 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Also, sigmodontines rodents show a variety of locomotory types, including generalized ambulatory as well as highly specialized forms (e.g., natatorial and fossorial) (Rodríguez-Serrano et al 2008;Rivas et al 2010;Carrizo et al 2014a). Despite this extraordinary ecological diversity, relatively few studies have been conducted to detect a possible correlation between the morphology of forelimb and locomotory types (Samuels and Van Valkenburgh 2008 and references therein;Carrizo and Díaz 2011;Carvalho Coutinho et al 2013;Carrizo et al 2014aCarrizo et al , 2014b. In this context, we analyzed the morphometric diversity of claws across 25 species of sigmodontines rodents with different locomotor types (ambulatory, fossorial, quadrupedal saltatorial, natatorial, and scansorial) to test if these ecological categories are characterized by different claw and forelimb skeleton morphologies and to test whether part of the variability of our data set is explained by phylogeny instead of adaptation.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the high diversity of Sigmodontinae and the remarkable ecological diversity, relatively few studies have been conducted on the locomotion modes and associated morphological variation in this group (Hershkovitz, , , , , , ; Stein, ; Voss, ; Neves, ; Rivas & Linares, ; Rivas‐Rodríguez et al. ; Carrizo & Díaz, ; Coutinho et al. ; Carrizo et al.…”
Section: Introductionmentioning
confidence: 99%
“…Stein (), Neves (), Rivas & Linares (), Rivas‐Rodríguez et al. () and Carrizo & Díaz () studied the variation of the postcranial skeleton of the sigmodontine rodents, as well as external characters, in order to relate them to the different locomotion modes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation